The Effect of Asphyxia on Neonatal Death: A Meta-Analysis - Silvalia Rahma Pratiwi; Hanung Prasetya; Bhisma Murti (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: